2013
DOI: 10.1002/oby.20173
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of prediction scores and novel biomarkers for predicting nonalcoholic fatty liver disease in obese children

Abstract: Background:Accurate prediction scores for liver steatosis are demanded to enable clinicians to noninvasively screen for nonalcoholic fatty liver disease (NAFLD). Several prediction scores have been developed, however external validation is lacking.Objective:The aim was to determine the diagnostic accuracy of four existing prediction scores in severely obese children, to develop a new prediction score using novel biomarkers and to compare these results to the performance of ultrasonography.Design and Results:Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 41 publications
1
59
0
1
Order By: Relevance
“…Several prediction scores have been developed for non-invasive liver steatosis screening, but they have insufficient diagnostic accuracy among obese children. 36 For DM, incidence, prevalence, and disease progression are believed to vary in different ethnic groups. The overall frequency of abnormal glucose homeostasis of 10% (8% impaired glucose tolerance and 2% with DM; data not shown) was lower than in a recent study by Brickman et al 16 who reported a 29% frequency of abnormal glucose homeostasis among a group of 8-to-14 years old, mainly of Hispanic and African American children with AN.…”
Section: Discussionmentioning
confidence: 99%
“…Several prediction scores have been developed for non-invasive liver steatosis screening, but they have insufficient diagnostic accuracy among obese children. 36 For DM, incidence, prevalence, and disease progression are believed to vary in different ethnic groups. The overall frequency of abnormal glucose homeostasis of 10% (8% impaired glucose tolerance and 2% with DM; data not shown) was lower than in a recent study by Brickman et al 16 who reported a 29% frequency of abnormal glucose homeostasis among a group of 8-to-14 years old, mainly of Hispanic and African American children with AN.…”
Section: Discussionmentioning
confidence: 99%
“…14 Details on these measurements were previously reported. 15 1 H-MRS determined liver steatosis and serum ALT were the primary outcome measures in this study. Treatment success was defined as absence of steatosis and/or normal ALT levels.…”
Section: Measurementsmentioning
confidence: 99%
“…However, large-scale abdominal ultrasounds may not be a cost-effective approach. Several circulating biomarkers and composite clinical scores including both clinical and circulating variables have been proposed as screening tools for NAFLD, but none of them proved to have higher accuracy and cost-effectiveness than ultrasounds [62]. Biopsy is also the gold-standard method to diagnose NASH and hepatic fibrosis.…”
Section: Markers Of Co-morbiditiesmentioning
confidence: 99%